UPAYA DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU DALAM MEMPROMOSIKAN TITUAL PETANG MEGANG - Tri Riska Rahmadilla; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Pekanbaru city has a beautiful and unique historical tourism. Yet media of promotion and publication about this historical tourism is not maximalized that the feedback from local society is lack. It cause unpopularity of the tourism. The department of culture and tourism pekanbaru city's role in promoting petangmegamg ritual is highly needed wether it is direct or through media so that society can be familiar with the meaning of the petang megang symbol. The purpose of this research is to find out the department's role in promoting petangmegang ritual.This is a qualitative descriptive research based on observation, interview and documentation. There are 12 informants in this research. Writer analyzed the data using interactive data analysis model with triangulasi and participation extention to check the validity of data.Result shows that the department's role to attract the society is in the form of brochures, baliho and spanduk, exhibition, photos, calendar events, external magazines, and local television station which is Riau Televisi. The role in promoting the petangmegang ritual is in the form of giving a good infrastructures, good relationship with printed and electronic media. Some of the society of pekanbaru understand the symbol of petang megang ritual, which is the thankfulness of people and the way of cleaning up body and soul in welcoming the holy month Ramadhan. This is a tradition from our anchestor that need to be saved.Key word: role, promotion, petang megang ritual